Generation of Multi-Transgenic Pigs Using PiggyBac Transposons Co-expressing Pectinase, Xylanase, Cellulase, β-1.3-1.4-Glucanase and Phytase - Wang, Haoqiang; Li, Guoling; Zhong, Cuili; Mo, Jianxin; Sun, Yue; Shi, Junsong; Zhou, Rong; Li, Zicong; Wu, Zhenfang; Liu, Dewu; Zhang, Xianwei (Frontiers in Genetics, 2020)
The current challenges facing the pork industry are to maximize feed efficiency and minimize fecal emissions. Unlike ruminants, pigs lack several digestive enzymes such as pectinase, xylanase, cellulase, β-1.3-1.4-glucanase, and phytase which are essential to hydrolyze the cell walls of grains to release endocellular nutrients into their digestive tracts. Herein, we synthesized multiple cellulase and pectinase genes derived from lower organisms and then codon-optimized these genes to be expressed in pigs. These genes were then cloned into our previously optimized XynB (xylanase)- EsAPPA (phytase) bicistronic construct. We then successfully generated transgenic pigs that expressed the four enzymes (Pg7fn (pectinase), XynB (xylanase), EsAPPA (phytase), and TeEGI (cellulase and β-glucanase)) using somatic cell cloning. The expression of these genes was parotid gland specific. Enzymatic assays using the saliva of these founders demonstrated high levels of phytase (2.0~3.4 U/mL) and xylanase (0.25~0.42 U/mL) activity, but low levels of pectinase (0.06~0.08 U/mL) activity. These multi-transgenic pigs are expected to contribute to enhance feed utilization and reduce environmental impact.